Sources of information on HIV/AIDS used by adolescents and young people: A scoping review protocol - Vanessa Carla do Nascimento Gomes Brito; Luzia Cibele de Souza Maximiano; Fernanda Belmiro de Andrade; Rogeria Moreira de Abrantes; Yenifer Lizeth Gañan Rojas; Jocellem Alves de Medeiros; Raissa Martins de Andrade; Elanna Nayele de Freitas Costa; Samuel da Silva Guedes; Beatriz de Oliveira Fernandes Felipe; Alexsandra Rodrigues Feijão (PLoS ONE, 2026)
Objective To describe the protocol for a scoping review of the main sources of information about HIV/AIDS used by adolescents and young people. Context Studies have shown that adolescents and young people are increasingly using digital technologies as a source of information about HIV/AIDS. Although these digital technologies offer potential benefits to the educational process, their implementation and use are not always free from challenges and implications. In this sense, it is essential to investigate the reliability of the information sources accessed by adolescents and young people. Design Scoping review protocol, conducted in accordance with JBI guidelines Method This is a protocol for a scoping review to be conducted following the JBI guidelines, in three phases and using the following data sources: Scopus, Cumulative Index to Nursing and Allied Health Literature, Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Web of Science and later, Google School, Capes Catalog of Theses and Dissertations, Theses Canada and USP Digital Library of Theses and Dissertations. The inclusion criteria are studies that address the theme, available in full, free of charge and without time or language restrictions. The exclusion criteria are opinion articles, letters to the editor and editorials. The results will be presented through discussions, tables, graphs and percentages. Expected results: The results are expected to reveal the main sources of information used by adolescents and young people regarding HIV/AIDS, allowing the identification of their preferences regarding the means and formats of access to content. This protocol is available for access through the following electronic address: https://osf.io/aunkh/ with https://doi.org/10.17605/OSF.IO/AUNKH . Conclusion Data analysis will help to identify potentialities and limitations in strategies for accessing information about HIV/AIDS by adolescents and young people. This scoping review can foster knowledge about information needs, guiding the creation of more effective content, supporting health decision-making and strengthening communication between professionals, users and institutions, contributing to the access of reliable data.